How Beautiful Girls’ Labor Becomes Leisure: The Relational Work of Elite Parties Participants - Banko, Anna (Journal of Economic Sociology, 2025)
The continuous increase in global income inequality has led to the public censure of big money to demonstrate social status. However, rich people can spend large amounts of money without moral hazard at elite parties. A book by Ashley Mears, a professor of sociology at Boston University and the University of Amsterdam, ‘Very Important People: Status and Beauty in the Global Party Circuit’ is an ethnography based on interviews and field observations at VIP parties. The author attended over one hundred parties in New York, Miami, the Hamptons, St Tropez and Cannes between 2011 and 2013. The book reveals the inner dynamics of VIP parties: their participants and the hierarchy between them, the meanings that actors invest in parties and in their relationships with other participants. It raises the issue of gender inequality and shows how in the context of this inequality actors find benefits for themselves, not always expressed in monetary terms. The review shows that the world of VIP parties is an aesthetic labor market. Here economic logic is deeply embedded in the social relations between actors. The concept of relational work is used to explain why the gender inequality between of male promoters and attractive girls is acceptable to actors. The process of relational work may be interesting for economic sociologists, along with the processes of accretion and conversion of various forms of capital. By applying these approaches, it is possible to offer an alternative to Ashley Mears’ critical discourse of relative gender inequality in the world of VIP. The conclusion speculates on what the world of VIP parties might look like in the Russian context.